L. Ranke’s and J. G. Droysen’s Conceptions of History - Juozaitis, Arvydas (Problemos, 1987)
The comparative analysis of the two theoretical stands is made in the article. It is revealed that the “non-party” objectivity of L. Ranke rests upon the forms of common sense and only by artificial means is promoted to the rank of abstract scientific character. Such a scientific character is exemplified in L. Ranke’s historical works, where world history is presented in its political reality. In the opposition to his precursor, J. G. Droysen bases his stand upon Descartes’ reflexion “cogito, ergo sum”. However, in the pure historical reconstruction the latter has no universal application and is confined to the psychological reception of the information from the past. As the result of the comparative analysis done, the logic of the scientific progress in the science of history is revealed.